General Vectorization of Line Objects in Drawn Maps - Tarabek, Peter (Communications - Scientific letters of the University of Zilina, 2009)
Drawn maps consist of multiple object types. The most important are line objects which represent infrastructure. Attributes of these objects are essential for many tasks but in raster format they provide only low level information. Vectorization must be used to obtain vector data. In this paper general vectorization process consisting of five stages is proposed. For these stages short discussion and basic recommendations are given and some proper methods are presented.